(Invited) P-Type Transparent Conducting Oxide Protection Layers for Sustainable Photoelectrochemical Water Oxidation. (13th April 2015) - Chen, Le; Yang, Jinhui; Lee, Lyman; Klaus, Shannon; Woods-Robinson, Rachel; Lum, Yanwei; Cooper, Jason K.; Sharp, Ian D.; Bell, Alexis T.; Ager, Joel W.
Abstract : In this paper, we propose that a p-type transparent conducting oxide (p-TCO) can function as a selective hole contact and corrosion protection layer on photoanodes used for light-driven water oxidation. To prove the concept, NiCo2 O4 was used as the p-TCO for n-Si protection in alkaline condition, and we show that this material has the requisite electronic structure, stability, transparency, and hole conductivity to achieve sustained and efficient solar water oxidation. The photoelectrochemical performance demonstrates the attractive combination of transparency and low-resistance hole conductivity in the NiCo2 O4 . Long-term testing indicates multi-day stability with minimal decrease in performance or observable corrosion of the Si photoanode. This works suggests that p-TCOs are promising as corrosion protection layers for stable water oxidation photoanodes.